Clinical Skills Development and Competency Assessment Needs among Nursing Assistant Students: A Design and Development Study - Lachezar Manchev; Gedamu Gebreamlak Hailu; Maurizio Martin Cavani Brain; Pichayaporn Ratt; Taisia Chertenko (Journal of Health Innovation and Environmental Education, 2026)
Purpose of the study: This study aimed to develop and validate a competency-based clinical skills development model for nursing assistant students and evaluate its effectiveness in improving clinical performance, procedural competence, and self-efficacy. Methodology: A Design and Development Research (DDR) approach with a sequential exploratory mixed-methods design was employed. Phase 1 involved qualitative needs assessment with 24 students and 6 clinical instructors to identify competency gaps. A competency-based learning model integrating structured simulation, standardized rubrics, DOPS-based formative feedback, and OSCE assessment was subsequently constructed and validated by seven experts (S-CVI = 0.92). Effectiveness was evaluated using a quasi-experimental pre-test–post-test control group design with 64. Outcomes included OSCE performance, DOPS ratings, and clinical self-efficacy. Data were analyzed using ANCOVA and effect size calculations. Main Findings: The intervention group demonstrated significantly higher post-test OSCE scores (82.6 ± 5.9 vs. 69.4 ± 6.7; p < 0.001; d = 1.95), improved DOPS ratings (4.3 ± 0.4 vs. 3.5 ± 0.5; p < 0.001), and increased self-efficacy (81.1 ± 7.5 vs. 64.3 ± 8.1; p < 0.001; d = 2.09) compared to controls. Skill retention at four weeks remained significantly higher in the intervention group (p < 0.001). Novelty/Originality of this study: Findings support structured operationalization of competency-based education in assistant-level nursing training and provide an empirically grounded framework for curriculum reform.